Ocean Acidification: Fish Physiology and Behavior - Joshua Patterson; Lisa Krimsky; Joseph Henry (EDIS)
Increased atmospheric carbon dioxide has led to increased levels of dissolved carbon dioxide in the oceans and acidified ocean water, which could have direct effects on the physiology and behavior of fishes. This 5-page fact sheet written by Joshua Patterson, Lisa Krimsky, and Joseph Henry and published by the UF/IFAS School of Forest Resources and Conservation, Program in Fisheries and Aquatic Sciences will summarize the current state of our understanding on the topic, with special emphasis on Florida fishes. It will also address current challenges in understanding the real-world effects of a complex global process using data largely collected on isolated fish in laboratory experiments. https://edis.ifas.ufl.edu/fa219